2022
DOI: 10.1155/2022/4857872
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Pertussis Vaccine Immunization during Pregnancy: A Meta-Analysis of Randomized Clinical Trials

Abstract: The objective of this meta-analysis is to assess the safety and immunogenicity of maternal pertussis vaccination based on randomized clinical trials. PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Internet, and Wan Fang Database were searched from inception up to the 8th of October 2021, using a protocol registered on PROSPERO with no. 42021287717, and a meta-analysis was conducted. We measured pooled geometric mean concentrations (GMCs) for IgG antibodies against pertussis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Regarding the safety of Tdap immunization during pregnancy, there is no evidence of an elevated risk of serious adverse events or stillbirth [72][73][74]. A retrospective cohort study from Canada also showed that prenatal Tdap exposure was not related to any adverse health problems in early childhood while it was associated with a decreasing trend in upper respiratory infections, gastrointestinal infections, and medical care requirement [75].…”
Section: Maternal Immunizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the safety of Tdap immunization during pregnancy, there is no evidence of an elevated risk of serious adverse events or stillbirth [72][73][74]. A retrospective cohort study from Canada also showed that prenatal Tdap exposure was not related to any adverse health problems in early childhood while it was associated with a decreasing trend in upper respiratory infections, gastrointestinal infections, and medical care requirement [75].…”
Section: Maternal Immunizationmentioning
confidence: 99%
“…Babies of vaccinated women were found to have higher transplacental antibodies against pertussis in the first 2 months of life [74]. A study comparing the immune responses against maternal immunization between preterm and term infants revealed that equal cord geometric mean concentrations (GMCs) of Ig G levels were observed in both groups.…”
Section: Maternal Immunizationmentioning
confidence: 99%
See 1 more Smart Citation